Oily Wastewater Remediation using Polyurethane Sponges Coated with an Optimised Amount of Graphene Nanoplatelets - Mitchell, Stella; Low, Jiun Hor; Yoon, Li Wan (Asia-Pacific Journal of Science and Technology, 2026)
Oily wastewater discharged into water bodies without proper treatment can endanger aquatic ecosystems and human health. This study explored an alternative method for treating oily wastewater using a graphene-nanoplatelet (GNP)-coated polyurethane (PU) sponge and reported its oil absorption performance. The PU sponge surface was modified by dip-coating it with 0 g, 0.5 g, 1 g, 1.5 g, 2 g, and 2.5 g GNP aqueous suspension to prepare a GNP-coated PU sponge. Fourier-transform infrared (FTIR) spectroscopy demonstrated that the GNP successfully coated onto the PU sponge surface. The GNP coating conferred a selective absorption ability to the PU sponges, which significantly enhanced their hydrophobicity and oleophilicity. The use of 1 g GNP achieved the highest oil absorption, which was approximately 44 times the original PU sponge mass. The morphological analysis confirmed that the GNP event dispersion on the PU sponge surface was the main reason for the oil absorption being highest at 1 g GNP. The results suggested that 1 g GNP should be used for modifying PU sponge surfaces for treating oily wastewater. Furthermore, the results provided fundamental knowledge and information that can facilitate the design and development of a GNP- and PU sponge-based material for treating oily wastewater.